Conception rate with or without hCG trigger in clomiphene induced cycles - Verma, Aruna; Gupta, Abhilasha; Kashyap, Monika; Meraj, Juveriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Clomiphene citrate (CC) is still the most common drug for ovulation induction. Most physicians use hCG trigger routinely for follicle rupture. Ideally hCG is recommended only where there is no spontaneous LH surge. Hence this study was conducted to see the role of hCG for follicle rupture in CC induced cycle. Aims and objectives of the study were to compare the ovulation rate in CC induced cycle with or without hCG trigger and finally the conception rate. Methods: Study was conducted in the department of OBG, LLRM medical college Meerut on women with anovulatory infertility. All women were given 50-100 mg CC. Follicular study from D-9 was done till follicle rupture. Women in group A were observed without any trigger and women in group B were given inj. hCG trigger 10,000 IU when follicle size reached 20-22 mm. Results: Conception rates were 25% Vs 31% in group A and group B. Follicle rupture was seen in 84% cases in group A and 71% in group B. Results were comparable in both the groups. Conclusions: By adding inj. hCG for ovulation trigger does not increase the conception rate. LH surge is already there in CC induced cycles. It is having role only in cases where no LH surge is there.